Investigating the dynamics of bank credit in Nigeria: The role of bank consolidation - Olorunsola E. Olowofeso; Abiodun S. Bada; Adeyemi A. Adeboye; Valli T. Adejo; Kufre J. Bassey; Kumafan S. Dzaan (CBN Journal of Applied Statistics, 2015)
This paper examines the dynamics of deposit money banks (DMB) credit and the role of consolidation in credit growth in Nigeria using vector error correction model and Granger causality test. The empirical investigation involved DMBs that have maintained a unique name and some market characteristics before and after the 2004 banking sector consolidation. Using quarterly data from 1999Q1 - 2013Q2 of the selected DMBs, the results show a positive relationship between post-consolidation credit supply growth and the real gross domestic product. The results also show that despite the onesided positive causality from credit supply to economic growth, the total contribution of the consolidated credit growth to real activity was not significant. The paper, therefore, recommends that in order to improve the credit channel of monetary policy transmission, policy makers should take into account how the banks react to such policies.
Keywords: E20; E51; E52; 330; Bank Consolidation; Credit Growth; Economic Activity; Monetary Policy